2002
DOI: 10.1200/jco.2002.04.140
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Trial of Temozolomide and Concurrent Radiotherapy in Patients With Brain Metastases

Abstract: Temozolomide is safe, and a significant improvement in response rate was observed when administered in combination with radiotherapy in patients with previously untreated brain metastases. A larger randomized trial is warranted to verify these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
165
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(178 citation statements)
references
References 28 publications
4
165
1
8
Order By: Relevance
“…WBI was gave as 40 Gy over 4 weeks, TMZ 75 mg/m2 per day, days 1-28; subsequent TMZ 200 mg/m2 per day, days 1-5/28-d cycle for six cycles but these results were not confirmed with brain metastases from lung cancer in phase III study conducted by the same authors (14,15).…”
Section: Discussion:-mentioning
confidence: 61%
See 1 more Smart Citation
“…WBI was gave as 40 Gy over 4 weeks, TMZ 75 mg/m2 per day, days 1-28; subsequent TMZ 200 mg/m2 per day, days 1-5/28-d cycle for six cycles but these results were not confirmed with brain metastases from lung cancer in phase III study conducted by the same authors (14,15).…”
Section: Discussion:-mentioning
confidence: 61%
“…However, individually, only one out of 7 randomized controlled trials RCTs included in this meta-analysis showed a some survival improvement following the addition of temozolomide to radiotherapy, with median survival times of 7and 8.6 months in the RT arm and TMZ plus RT arm, respectively (15). In four randomized controlled trials that compare radiotherapy to concomitant TMZ and RT, the OS was lower in patients who were treated with combination TMZ and RT (11,(19)(20)(21) It is hard to compare the results of our study, that was performed on a homogenous group of patients ;with the previously mentioned studies which included more heterogeneous groups of patients and with different treatment regimens.…”
Section: Discussion:-mentioning
confidence: 99%
“…Antonodau et al in a randomized phase II study and in a confirmatory phase III study comparing TMZ plus WBRT to WBRT alone in population largely consisting of lung cancer patients, reported a significantly greater overall response in the patients receiving TMZ [25,26]. Instead, in a preliminary report of Verger et al, a response of only 16% was noted with WBRT plus TMZ in 85 patients, half of whom had lung cancer [27].…”
Section: Discussionmentioning
confidence: 98%
“…WBRT is the most common and effective standard treatment for lung cancer patients with multiple brain metastases or lesions that are inoperable (Antonadou et al, 2002;Guerrieri et al, 2004;Verger et al, 2005). WBRT can rapidly relieve neurologic symptoms caused by BM, control the local progression of metastasis, improve the neurological function and quality of life, and prolong progression free survival time of these patients (Postmus et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…WBRT can rapidly relieve neurologic symptoms caused by BM, control the local progression of metastasis, improve the neurological function and quality of life, and prolong progression free survival time of these patients (Postmus et al, 2000). However, WBRT may cause radioactive nerve damage, even lead to brain atrophy and necrosis (Antonadou et al, 2002;Gijtenbeek et al, 2011), which is particularly a concern in large doses of radiation. The limitation on the dose of WBRT makes it difficult to completely eradicate the tumor.…”
Section: Discussionmentioning
confidence: 99%